2005
DOI: 10.1128/jb.187.20.7103-7118.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Program of Early Sporulation and Stationary-Phase Events in Clostridium acetobutylicum

Abstract: DNA microarray analysis of Clostridium acetobutylicum was used to examine the genomic-scale gene expression changes during the shift from exponential-phase growth and acidogenesis to stationary phase and solventogenesis. Self-organizing maps were used to identify novel expression patterns of functional gene classes, including aromatic and branched-chain amino acid synthesis, ribosomal proteins, cobalt and iron transporters, cobalamin biosynthesis, and lipid biosynthesis. The majority of pSOL1 megaplasmid genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
175
3
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(202 citation statements)
references
References 103 publications
23
175
3
1
Order By: Relevance
“…suppression of the tricarboxylic acid cycle, cobalamin biosynthesis, DNA replication, and induction of stress response proteins (43)(44)(45)(46). The transcriptional suppression of the septum formation component FtsZ and DNA replication machinery DnaB could be directly attributed to the cellular elongation and growth inhibition for the mutant (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…suppression of the tricarboxylic acid cycle, cobalamin biosynthesis, DNA replication, and induction of stress response proteins (43)(44)(45)(46). The transcriptional suppression of the septum formation component FtsZ and DNA replication machinery DnaB could be directly attributed to the cellular elongation and growth inhibition for the mutant (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…In S. aureus, this leads to upregulation of all four agr genes. In C. acetobutylicum, on the other hand, although adjacent, agrBD and agrCA are predicted to form independent transcriptional units [31] and, accordingly, transcriptome data of [17] illustrate that only transcripts of agrBD are significantly increased at stationary phase. Thus the evidence suggests that quorum sensing feedback into agrCA is absent in C. acetobutylicum.…”
Section: The Agr Operonmentioning
confidence: 99%
“…Previous modelling studies have suggested that feedback into the two-component system is the key to a fully effective quorum-sensing system [16], but, interestingly, these two feedback loops appear to be absent in C. acetobutylicum [17]. Comparisons with the staphylococcal agr system indicate that, depending upon the mechanism of interaction between the agr system and the sporulation-initiation network, the clostridial agr circuitry may (at least in part) be in place either to moderate the number of spores that are formed (in order for this number to reflect the urgency of the situation), or simply as an energy-saving strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Association analysis of both sets of data, transcriptional and metabolite profiles, led to the identification of targets for further metabolic engineering. Microarray-based transcriptome analysis in engineering solvent (butanol) tolerance (71,72) and identification of genetic determinants contributing to a variety of phenotypes is reported in the literature (68,(73)(74)(75)(76)(77)(78)(79)(80)(81)(82).…”
Section: Analysis At Genomic and Population Scalementioning
confidence: 99%